The Diagnostic Value of N-Acetyl-β-D-Glucosaminidase and Microalbumin Concentrations in Rheumatoid Arthritis - Spasovski, Dejan; Gruev, Todor; Marina, Nada; Calovski, Jordan; Percinkova, Snežana; Osmani, Baskim; Rajčevska, Ljubinka; Cakalaroski, Kočo; Sotirova, Tatjana; Balkanov, Svetlana; Slaninka-Micevska, Maja (Centre for Evaluation in Education and Science (CEON/CEES), 2007)
The Diagnostic Value of N-Acetyl-β-D-Glucosaminidase and Microalbumin Concentrations in Rheumatoid ArthritisThe purpose of this research was to compare the diagnostic values of laboratory variables, to present quantitative evaluations of the diagnostic sifted test with reference to sensitivity and specificity, the predictive value of the positive and negative test and precision of the test for N-acetyl-β-D-glucosa-minidase (NAG), microalbumin, rheumatoid factor (RF), Creactive protein (CRP), DAS 28 index, in early diagnosis of untreated rheumatoid arthritis (RA), and to define the effect of untreated rheumatoid arthritis on glomerular and tubular function. Using a colorimetric assay for the determination of Nacetyl-β-D-glucosaminidase and an immunoturbidimetric assay for the determination of urinary albumin, the samples of serum and urine have been examined in 70 participants (35 RA who were not treated, 35 healthy controls). RF was defined with the test for agglutination (Latex RF test) in the same participants. Out of 35 examined patients with RA, in 13 we found the presence of NAG enzymuria (sensitivity of the test 37.14%), while microalbuminuria appeared in 4 patients (sensitivity of the test 11.42%). RF appeared in 17 patients (sensitivity of the test 48.57%). Four patients were NAG and RF positive, while 3 patients were microalbuminuria and RF positive. Among 18 RF negative patients, 9 patients were NAG positive, and 1 patient presented with microalbuminuria. Among 17 RF positive RA, the presence of NAG was found in 4 patients, and the presence of microalbuminuria in 3 patients. Among 18 RF negative RA, NAG enzymuria appeared in 9 patients. Microalbuminuria was present in 1 patient. In the healthy control group, 8 patients were NAG positive, 2 patients were positive for microalbuminuria. RF appeared in 2 patients. NAG has higher sensitivity than microalbuminuria in the detection of asymptomatic renal lesions in untreated RA.